2020
DOI: 10.1093/ibd/izaa224
|View full text |Cite
|
Sign up to set email alerts
|

90-Day Specific Readmission for Clostridium difficile Infection After Hospitalization With an Inflammatory Bowel Disease Flare: Outcomes and Risk Factors

Abstract: Background Patients with inflammatory bowel disease (IBD) have an increased risk for Clostridium difficile infection (CDI) and carry significantly higher morbidities and mortality than those without IBD. We aimed to investigate disease-specific readmission rates and independent risk factors for CDI within 90 days of an index hospitalization for an IBD flare. Methods The Nationwide Readmission Database was queried for the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Patients with IBD who have CDI have worse long-term clinical outcomes (including UC-related hospitalizations, failure of immunosuppression, emergency visits, and the need for colectomy) compared with CDI negative patients at 1 year after the initial admission. 6 , 8 , 12 , 21 23 …”
Section: Clinical Features and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with IBD who have CDI have worse long-term clinical outcomes (including UC-related hospitalizations, failure of immunosuppression, emergency visits, and the need for colectomy) compared with CDI negative patients at 1 year after the initial admission. 6 , 8 , 12 , 21 23 …”
Section: Clinical Features and Outcomesmentioning
confidence: 99%
“…Patients with IBD who have CDI have worse long-term clinical outcomes (including UC-related hospitalizations, failure of immunosuppression, emergency visits, and the need for colectomy) compared with CDI negative patients at 1 year after the initial admission. 6,8,12,[21][22][23] Data from the NIS from 1993 to 2003 for all IBD patients with CDI demonstrated that the case fatality for UC patients with C. difficile was 8.5% and was especially high (⩾25%) in patients who underwent routine intestinal surgery. 24 Patients with both CDI and IBD have a longer hospital length of stay by 3 days than those with IBD but without CDI.…”
Section: Clinical Features and Outcomesmentioning
confidence: 99%
“… 19 We found that CD patients in group A2 were more likely to have CDI than group A3, the occurrence rates were 17.05% and 6.67%, respectively. CDI could increase the health care burden and 90-day CDI-specific readmission rate of IBD, 20 and it could increase the risk of surgery by depleting the beneficial fecal microbiome and methionine biosynthesis. 21 …”
Section: Discussionmentioning
confidence: 99%
“…However, in specific patient populations, age was often not related to CDI risk. For example, age was a significant risk factor in only two of four studies in patients receiving solid organ transplants [28,[39][40][41], one of three studies in patients with bowel disease [42][43][44], and one of four studies in patients with cancer [45][46][47][48].…”
Section: Risk Factors For CDImentioning
confidence: 99%